Reference ranges for antiepileptic drugs revisited: a practical approach to establish national guidelines - Reimers A; Berg JA; Burns ML; Brodtkorb E; Johannessen SI; Johannessen Landmark C (Dove Medical Press, 2018)
Arne Reimers,1,2 Jon Andsnes Berg,3 Margrete Larsen Burns,4 Eylert Brodtkorb,5,6 Svein I Johannessen,6,7 Cecilie Johannessen Landmark4,7,8 1Department of Clinical Pharmacology, St Olavs University Hospital, Trondheim, Norway; 2Department of Clinical and Molecular Medicine, Norwegian University of Science and Technology (NTNU), Trondheim, Norway; 3Laboratory of Clinical Biochemistry, Section of Clinical Pharmacology, Haukeland University Hospital, Bergen, Norway; 4Department of Pharmacology, Section for Clinical Pharmacology, The National Center for Epilepsy, Oslo University Hospital, Oslo, Norway; 5Department of Neurology and Clinical Neurophysiology, St Olavs University Hospital, Trondheim, Norway; 6Department of Neuromedicine and Movement Science, Norwegian University of Science and Technology, Trondheim, Norway; 7The National Center for Epilepsy, Oslo University Hospital, Oslo, Norway; 8Programme for Pharmacy, Faculty of Health Sciences, Oslo Metropolitan University, Oslo, Norway Background and objective: Laboratories sometimes use different reference ranges for the same antiepileptic drug (AED), particularly for new and poorly investigated drugs. This may contribute to misunderstandings, concerns or inappropriate dose changes, which in turn may affect therapeutic effect, drug safety or treatment adherence. Therefore, the Norwegian Association of Clinical Pharmacology wished to update and harmonize the reference ranges for AEDs and establish national guidelines for Norway. Methods: A working group collected information on the reference ranges used by Norwegian laboratories for all commonly used AEDs. These reference ranges were compared to recent recommendations by the International League Against Epilepsy, current literature, applicable clinical studies, reference ranges used by leading Northern European epilepsy centers outside of Norway, and routine data derived from Norwegian laboratory databases. Results: Reference ranges varied between laboratories for four of 23 available AEDs (lamotrigine, valproate, eslicarbazepine and oxcarbazepine). For four AEDs (brivaracetam, perampanel, stiripentol and sulthiame), reference ranges had not previously been established. In total, 13 reference ranges were either harmonized, updated or newly established. No changes were applied to the remaining 10 AEDs. Conclusion: Updated and harmonized reference ranges are now available for 22 of the 23 AEDs available in Norway. The exception is vigabatrin (reference range not applicable). Revision of reference ranges is an important part of pharmacovigilance of AEDs and must be a continuous process based on current literature and clinical experience. Keywords: antiepileptic drug, serum concentration, reference range, therapeutic drug monitoring